Fast Hydrophobicity Recovery of the Surface-Hydrophilic Poly(dimethylsiloxane) Films Caused by Rechemisorption of Dimethylsiloxane Derivatives - Senzai, Takahiro (Langmuir : the ACS journal of surfaces and colloids, 2019)
Long-term stability of the surface hydrophilicity of poly(dimethylsiloxane) (PDMS) remains a critical issue for a wide range of applications including, e.g., biomedical materials, biochip devices, and microfluidics. Although several mechanisms for recovering hydrophobicity have been proposed, none has been proven unequivocally. We discovered that the hydrophobic recovery of surface-oxidized PDMS films was accelerated when the films were stored in a closed chamber under an atmosphere containing dimethylsiloxane derivatives such as octamethylcyclotetrasiloxane, which had evaporated from the films and were detected by gas chromatography-mass spectrometry measurements. X-ray photoelectron spectroscopy and quartz crystal microbalance measurements were used to monitor the chemical deposition of the derivatives on the surface-oxidized substrates, and the formation of a hydrophobic dimethyl silicone layer rendered the oxidized surfaces hydrophobic again. In the absence of superficial hydrophilic functional groups, volatile species did not react with the surface, and the hydrophobic dimethyl silicone layer did not form. The results show that the formation of a thin layer of dimethylsiloxane derivatives by chemisorption is a new mechanism for recovering the surface hydrophobicity of PDMS films